Kemiskinan dan Ketimpangan Melalui Prevelensi Ketidakcukupan Konsumsi Masyarakat di Indonesia - Riza Nabila; Irranda Putra Syahna; Khopifah Indah Daulay; Sari Wulandari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Poverty is a person's inability to meet the needs of everyday life. Poverty is a serious problem that must be addressed immediately. One of the causes of poverty is because there are differences between income and expenditure levels that occur in various regions, this is what is known as inequality. The prevalence of insufficient public consumption is a condition in which people are unable to meet their needs properly and healthily. This is closely related to poverty. Because, if there is no poverty, it is possible that people's consumption will be fulfilled. This study uses a qualitative method in the literature approach. This research aims to examine more deeply related to poverty and inequality in Indonesia through the prevalence of insufficient consumption of the Indonesian people. The results of this study show that the poverty and inequality rates in Indonesia since March 2022 and the insufficient public consumption will also decrease. the insufficient consumption of the Indonesian people in terms of food consumption has increased from 2019 around 7.63, 2020 around 8.43 until 2021 it reaches 8.49. Keywords: poverty, inequality, inadequacy society